Student Tolerance through Religious Moderation Values in Aswaja Courses - Ashoumi, Hilyah; Hidayatulloh, M Kris Yuan; Hasanah, Siti Da’watul; Umami, Fahmi Najah (Universitas Islam Negeri Raden Intan Lampung, 2023)
The purpose of this study is to describe the process of internalisation of religious moderation values in Aswaja course and its implication on students' tolerance attitude. This research is included in research that uses a phenomenological approach using qualitative research. This approach requires a number of assumptions that are different from the way used to approach people's behaviour with the intention of finding